The six electric fault zone analysis for predictive maintenance on motors of the continuous production - Arttama, Kritsakorn; Jettanasen, Chaiyan (My University, 2022)
This paper proposes for motor health analysis by classifying into six fault zones. These consist of power quality, power circuit, insulation, stator, rotor, and air gap. First of all, power quality would consider on the quantity between voltage and current. Secondly, power current plays a role on the current supplied to the motor. Thirdly, insulation would take a focus on insulation's health among windings and ground. Fourth, stator condition concerns insulation of windings, solder joints between the coils and the stator core. Fifth, rotor focuses on the condition of both rotor cage and lamination. Lastly, air gap would mainly concern concentricity between rotor and stator. All of these fault zones would be diagnosed for condition-based monitoring with the aims to prevent any premature damage on motor and also to saves maintenance costs.
Keywords: Current analysis; Fault zone; Motor failure; Power quality